PENGEMBANGAN LEMBAR KERJA MAHASISWA (LKM) BERBASIS LIVEWORKSHEET PADA MATERI SISTEM EKSKRESI - Nurmiati Nurmiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
This research aims to develop and describe student worksheet on the excretory system materials. This research is an R&D (Research and Development) study based on the ADDIE development model, which consist of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The research instruments used were validation sheet question and response quesionnaires. The students worksheet was validated by 3 experts: a subject matter expert, a media expert, and a biology lecturer and it was tested on students.The result showed the students worksheet the percentage of achievements was 90% according material expert, 94% according media expert, and 96% according biolgy lecturer. Meanwhile, the student testis resulted in a score of 83,9% with a very feasible criteria. The conclusion of this research is that student worksheet based liveworksheet on the excretory system are highly suitable for supporting the learning process